Morbidly Obese Patients Undergoing Reduced Cup Anteversion Through a Direct Lateral Approach. (4th May 2016) - Brodt, Steffen; Jacob, Benjamin; Windisch, Christoph; Seeger, Joern; Matziolis, Georg
Abstract : Background: The presence of obesity negatively affects the results after total hip arthroplasty. The influence of morbid obesity on cup positioning is investigated. Methods: A retrospective analysis of radiographs from 790 patients in 2013 and 2014 was performed. The correlation of cup inclination and anteversion with body mass index (BMI) was analyzed. Three groups were formed: 139 patients with normal weight (BMI of <25 kg/m 2 ), 566 patients with moderate obesity (BMI between 25 and 34 kg/m 2 ), and 85 patients with morbid obesity (BMI of ≥35 kg/m 2 ). Results: Cup anteversion significantly correlated with BMI (R = −0.127, p < 0.001) and patient age (R = 0.115, p = 0.001). This corresponded with a reduction of anteversion by 3.4° (p < 0.001) in the morbidly obese group compared with the normal-weight group. Cup inclination was not influenced by BMI or patient age. Conclusions: The precision of cup positioning declines with increasing obesity. In addition, significantly reduced anteversion is found in younger patients. We assume that this is due to iatrogenically changed pelvic tilt resulting from increased pressure exerted on the dorsal and ventral acetabular rim retractors. Level of Evidence: PrognosticLevel III . See Instructions for Authors for a complete description of levels of evidence.